2021
DOI: 10.3832/ifor3748-014
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of technological properties of matá-matá wood (Eschweilera coriacea [DC.] S.A. Mori, E. odora Poepp. [Miers] and E. truncata A.C. Sm.) by Near Infrared Spectroscopy

Abstract: Biogeosciences and Forestry Biogeosciences and Forestry Characterization of technological properties of matá-matá wood (Eschweilera coriacea [DC.] S.A. Mori, E. odora Poepp. [Miers] and E. truncata A.C. Sm.) by Near Infrared Spectroscopy Cristiano Souza do Nascimento (1) , Claudete Catanhede do Nascimento (2) , Roberto Daniel de Araújo (2) , Jose Carlos Rodrigues Soares (3) , Niro Higuchi (4)The aim of this study was to determine the technological properties (chemical, mechanical and physical) of Eschweilera s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 27 publications
(42 reference statements)
0
0
0
Order By: Relevance
“…Among the central woods are Manilkara huberi, Bowdichia sp., Caryocar villosum, and Piptadenia suaveolens (Teixeira et al 2019). Studies have shown the potential of NIR to predict the basic density of the wood from native species (Pace et al 2019;Nascimento et al 2021). This indicates that obtaining wood density through non-destructive monitoring is a crucial step to simplify and optimize the management routine of forestbased companies, allowing greater predictability of the technological behavior of their products.…”
Section: Introductionmentioning
confidence: 99%
“…Among the central woods are Manilkara huberi, Bowdichia sp., Caryocar villosum, and Piptadenia suaveolens (Teixeira et al 2019). Studies have shown the potential of NIR to predict the basic density of the wood from native species (Pace et al 2019;Nascimento et al 2021). This indicates that obtaining wood density through non-destructive monitoring is a crucial step to simplify and optimize the management routine of forestbased companies, allowing greater predictability of the technological behavior of their products.…”
Section: Introductionmentioning
confidence: 99%